Whole-Exome Sequencing of Rare Site Endometriosis-Associated Cancer - Kurose, Sonomi; Nakayama, Kentaro; Razia, Sultana; Ishikawa, Masako; Ishibashi, Tomoka; Yamashita, Hitomi; Sato, Seiya; Sakiyama, Asuka; Yoshioka, Shinya; Kobayashi, Misa; Nakayama, Satoru; Otuski, Yoshiro; et al. (Diseases, 2021)
Malignant transformation of extraovarian endometriosis is rare, with the carcinogenesis mechanism unclear. To clarify the actionable variants of rare-site endometriosis-associated cancer (RSEAC), we performed whole-exome sequencing for the tumor, in two patients. The intestine was affected in both cases, although the histology was that of clear cell carcinoma and undifferentiated carcinoma, respectively. Therefore, the cases were referred to as endometriosis-associated intestinal tumors (EIATs). Actionable variants (all frameshift mutations) were identified in tumor suppressor genes ARID1A, PTEN, and p53; however, no oncogenic variants were identified. Both cases were microsatellite stable. The patient with undifferentiated carcinoma exhibited hypermutator and homologous recombination deficiency phenotypes. The dominant mutation signatures were signature 30 (small subset of breast cancers) and 19 (pilocytic astrocytoma) in patient 1, and signature 5 (small subset of breast cancers) and 3 (breast, ovarian, and pancreatic cancers) in patient 2. Immunohistochemistry revealed positive CD8 and PD-1 expression in both patients; patient 1 also showed positive PDL-1 expression. Our results suggest that RSEAC is associated with variants of tumor suppressor genes as epigenetic alterations. Mutation signature-based whole-exome sequencing could be useful to select an adjuvant chemotherapy regimen. High CD8 and PD-1 expression in RSEAC suggests that immune checkpoint inhibitors are useful for treatment.